Interferon Alpha Favors Macrophage Infection by Visceral Leishmania Species Through Upregulation of Sialoadhesin Expression - Van Bockstal, Lieselotte; Bulté, Dimitri; Van den Kerkhof, Magali; Dirkx, Laura; Mabille, Dorien; Hendrickx, Sarah; Delputte, Peter; Maes, Louis; Caljon, Guy (Frontiers in Immunology, 2020)
Type I interferons (IFNs) induced by an endogenous Leishmania RNA virus or exogenous viral infections have been shown to exacerbate infections with New World Cutaneous Leishmania parasites, however, the impact of type I IFNs in visceral Leishmania infections and implicated mechanisms remain to be unraveled. This study assessed the impact of type I IFN on macrophage infection with L. infantum and L. donovani and the implication of sialoadhesin (Siglec-1/CD169, Sn) as an IFN-inducible surface receptor. Stimulation of bone marrow-derived macrophages with type I IFN (IFN-α) significantly enhanced susceptibility to infection of reference laboratory strains and a set of recent clinical isolates. IFN-α particularly enhanced promastigote uptake. Enhanced macrophage susceptibility was linked to upregulated Sn surface expression as a major contributing factor to the infection exacerbating effect of IFN-α. Stimulation experiments in Sn-deficient macrophages, macrophage pretreatment with a monoclonal anti-Sn antibody or a novel bivalent anti-Sn nanobody and blocking of parasites with soluble Sn restored normal susceptibility levels. Infection of Sn-deficient mice with bioluminescent L. infantum promastigotes revealed a moderate, strain-dependent role for Sn during visceral infection under the used experimental conditions. These data indicate that IFN-responsive Sn expression can enhance the susceptibility of macrophages to infection with visceral Leishmania promastigotes and that targeting of Sn may have some protective effects in early infection.